1994
DOI: 10.1177/0310057x9402200507
|View full text |Cite
|
Sign up to set email alerts
|

Premedication with Oral Midazolam in Children—an Assessment of Psychomotor Function, Anxiolysis, Sedation and Pharmacokinetics

Abstract: We studied 30 children, aged 4 to 12 years, undergoing elective circumcision, premedicated with midazolam 0.5 mg.kg-I and atropine 0.02 mg.kg-I by mouth. A modified postbox test and the coding component of the Wechsler intelligence scale (WISC-R) was used to assess the preoperative effect of premedication on psychomotor function. Mood and sedation were also scored and related to serum midazolam concentrations. The children showed a significant decline in psychomotor performance 30 and 60 minutes after premedic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 22 publications
(8 reference statements)
1
7
0
1
Order By: Relevance
“…In terms of making children cooperate without falling asleep, The values are numbers for the recovery scale and means ± SD for the time to emergence * P < 0.05 vs. group 1; † P < 0.05 vs. group 2; ‡ P < 0.05 vs. group 3 these results are comparable to those in other reports that investigated the effect of oral midazolam premedication [1,2,13]. After midazolam is administered orally, its serum concentration peaks after 50-60 min and sometimes remains at therapeutic levels for anxiolysis and light sedation up to 2 h after administration [17,18]; this interval coincides with the recovery period from brief anesthesia seen in our study. Therefore, we believe that the residual effects of midazolam still exist on emergence from anesthesia and can be adequately reversed by flumazenil.…”
Section: Discussionsupporting
confidence: 83%
“…In terms of making children cooperate without falling asleep, The values are numbers for the recovery scale and means ± SD for the time to emergence * P < 0.05 vs. group 1; † P < 0.05 vs. group 2; ‡ P < 0.05 vs. group 3 these results are comparable to those in other reports that investigated the effect of oral midazolam premedication [1,2,13]. After midazolam is administered orally, its serum concentration peaks after 50-60 min and sometimes remains at therapeutic levels for anxiolysis and light sedation up to 2 h after administration [17,18]; this interval coincides with the recovery period from brief anesthesia seen in our study. Therefore, we believe that the residual effects of midazolam still exist on emergence from anesthesia and can be adequately reversed by flumazenil.…”
Section: Discussionsupporting
confidence: 83%
“…Orally administered Midazolam has been reported in the literature to be a safe and effective induction agent in infants and children and can be used successfully for short-term procedures.8-20 It is a suitable preoperative agent for producing anxiolysis, but in order for it to be effective, it must be given in a relatively large dosage per body weight (0.5 mg-0.75 mg/kg). 21,22 Sedative doses minimally depress respiration or cardiovascular function, but respiratory depression and hypotension can occur. Dysphoria and loss of coordination are also associated risks.…”
mentioning
confidence: 99%
“…Dysphoria and loss of coordination are also associated risks. 21 The effects23 of Midazolam can be easily reversed within minutes with intravenously administered flumaxenil, a benzodiazepine-reversing agent. ducted using dosages ranging from 0.25 mg/kg, 0.5 mg/kg, to 0.75 mg/kg oral Midazolam as a preoperative sedative agent.…”
mentioning
confidence: 99%
“…Jones et al also reported adequate sedation and anxiolysis 30-60 min after 0.5 mg/kg oral premedication. 12 On the other hand, Payne et al found superior amnesia after 0.45 mg/kg oral midazolam (60%) as compared to an oral mixture of 2 mg/kg trimeprazine, 0.1 mg/kg methadone and 0.15 mg/kg droperidol (43%) or the placebo (16%) and the amnesia was equal to 0.15 mg/kg intramuscular midazolam premedication. 13 The pre-medication times were not specified in this study.…”
Section: Discussionmentioning
confidence: 98%